The Impact of Internet Use on Informal Entrepreneur Welfare: The Case of Services Sector in Indonesia - Rachmatullah, Yuda Bagus; Santoso, Dwi Budi; Satria, Dias (AIBPM Publisher, 2023)
The services sector is a very important one which has the largest percentage of informal entrepreneurs compared to other sectors in Indonesia. However, this sector experienced the most significant decrease in welfare due to the pandemic attack in 2020. Using the 2020 National Labor Force Survey (Sakernas) data, this study aims to link the role of internet use, which was highly developed during the pandemic, to increasing the welfare of informal entrepreneurs in the services sector. Based on the results of binary logistic regression, (1) The use of the internet, especially for the purpose of transaction activities, has the greatest influence in supporting the welfare of informal services sector entrepreneurs, and (2) Opportunities to obtain higher welfare are owned by male entrepreneurs, with ever-married status, are more educated, have white-collar and gray-collar types of work, have skills, and live in areas with better infrastructure. Therefore, it is necessary to have a program to increase digital literacy, especially in activities that support business activities which can be carried out through training or mentoring, especially for services sector entrepreneurs who have a lower level of education, are less skilled, and for areas with a lower level of infrastructure.